2020
DOI: 10.1038/s41588-020-0599-0
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of 542,934 subjects of European ancestry identifies new genes and mechanisms predisposing to refractive error and myopia

Abstract: Refractive errors, in particular myopia, are a leading cause of morbidity and disability worldwide and their prevalence is rising, largely due to cultural and environmental changes. Genetic investigation is a valuable tool to better understand the molecular mechanisms underlying abnormal eye development and impaired vision. We conducted a meta-analysis of genome-wide association studies involving 542,934 European participants and identified 336 novel genetic loci associated with refractive error that explain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
331
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 208 publications
(350 citation statements)
references
References 79 publications
(117 reference statements)
12
331
7
Order By: Relevance
“…73 Further, another recent meta-analysis of human genome-wide association studies of refractive errors, applying Gene Ontology, identified "Circadian Rhythm" and "Circadian Regulation of Gene Expression" as two of the enriched gene sets. 74 Besides clinical genetics, the results here and our prior findings on altered clock and circadian rhythm-related genes in myopia, 15,16,48 support the possibility that the circadian clock and melanopsin may provide the mechanistic link between environmental light exposures and refractive development. 13…”
Section: Light and Refractionsupporting
confidence: 72%
“…73 Further, another recent meta-analysis of human genome-wide association studies of refractive errors, applying Gene Ontology, identified "Circadian Rhythm" and "Circadian Regulation of Gene Expression" as two of the enriched gene sets. 74 Besides clinical genetics, the results here and our prior findings on altered clock and circadian rhythm-related genes in myopia, 15,16,48 support the possibility that the circadian clock and melanopsin may provide the mechanistic link between environmental light exposures and refractive development. 13…”
Section: Light and Refractionsupporting
confidence: 72%
“…Seasonal changes reported in myopia progression could also suggest an impact of seasonal variations of circadian rhythms on the development of myopia 46 . Evidence supporting a role of circadian rhythm in myopia development is further strengthened by the results from a recent metaanalysis of genome-wide association studies, where genetic factors regulating circadian rhythm are identified to also participate in the development of myopia and refractive error 15 . Finally, yet importantly, several ocular biometry parameters, such as intraocular pressure (IOP), choroidal thickness, and axial length, were found to exhibit diurnal rhythms in humans 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Supportive of the hypotheses presented by Chakraborty et al, 23 recent work demonstrates that knockout of the circadian gene Bmal1 in the mouse retina or the circadian genes cycle and period in Drosophila melanogaster both result in myopic phenotypes, 24 and findings from a recent meta-analysis of genome-wide association studies suggest that genetic factors that control circadian rhythms are involved in human myopia development. 25 Circadian rhythms are biological processes that display an endogenous, entrainable oscillation of approximately 24 hours. In humans, these rhythms form a hierarchy of oscillators, orchestrated by a central pacemaker located in the suprachiasmatic nuclei (SCN), to synchronize our physiology and behaviors to the changing demands of the daynight cycle.…”
mentioning
confidence: 99%
“…Supportive of the hypotheses presented by Chakraborty et al, 23 recent work demonstrates that knockout of the circadian gene Bmal1 in the mouse retina or the circadian genes cycle and period in Drosophila melanogaster both result in myopic phenotypes, 24 and findings from a recent meta-analysis of genome-wide association studies suggest that genetic factors that control circadian rhythms are involved in human myopia development. 25 …”
mentioning
confidence: 99%